Development of Stand Alone Interactıve E-Modules on the Subject of Fundamentals of Network Engıneerıng and Telecommunıcatıons in SMK Imelda Medan - Marlina Nasution; Nizwardi Jalinus; Dedy Irfan; M Giatman; Lasyatta Syaifullah (Jurnal Penelitian Pendidikan IPA, 2025)
The development of interactive learning media is an urgent need at SMK Imelda Medan, especially in the subject of Fundamentals of Network Engineering and Telecommunications. This research aims to develop a standalone interactive E-Module that is valid and effective to improve student learning outcomes. The method used is Research and Development (R&D) with the 4-D model (define, design, develop, disseminate), involving experimental and control classes. The research sample consisted of 108 students of class X Computer and Network Engineering Expertise Programme, selected through purposive sampling. Data analysis included validity, reliability, effectiveness, and statistical tests such as Kolmogorov-Smirnov, Levene, MANOVA, and effect size calculation. The validation results showed that the E-Module was valid and reliable with a loading factor value > 0.7, AVE > 0.5, and reliability value > 0.8. The average score of experimental class students was higher (86.04), especially in practice with a difference of 10.67 points. The paired sample t-test showed a significant difference (p < 0.001) with a very large effect size (Cohen's d > 1.8). MANOVA confirmed significant multivariate differences. This study proved the high effectiveness of the E-Module and made theoretical, practical, and pedagogical contributions to digital learning in vocational education.